Determinants of non-performing loan in Malaysia Banks / Nur Aishah Zuraimi - Zuraimi, Nur Aishah (Faculty of Business and Management, 2018)
This research is about non-performing loan in Public, Alliance, Hong Leong, and Maybank Banks and used panel data and pool regressions for the period 2002 until 2016. It is important to identify the problem that may leads to non-performing loan because it will affect the ability to perform in development of the economy. The independent variables used are the interest rates, liabilities, lending and borrowing and gross domestic product (GDP). This study was limited to four variables as the causes of non-performing loan in Malaysia Banks. Two banks are selected for data collection and whole data was used is secondary data. The interpretation of these results as concerns to the causes of non-performing loans should be restricted to variables under study. The study only covered commercial banks in Malaysia and did not consider other financial institutions across the study countries so as to provide a more broad based analysis. Few studies have been done on causes and management of nonperforming loan in Malaysia. Keywords: Non-Performing Loans (NPL), Interest Rates, Lending and Borrowing, Gross Domestic Product (GDP).